Spectroscopic observation of triplet exciton dynamics during operation in polymer light emitting diodes. (12th April 2016) - Takahashi, Takahiro; Kanemoto, Katsuichi
Abstract: In typical fluorescent organic light emitting diodes (LEDs), the observation of triplet excitons is difficult because of their non-radiative features of decay. The generation process of triplet excitons was successfully monitored by employing spectroscopic techniques combined with LED operation. The generation dynamics of singlet excitons are then simultaneously examined by time-resolved electroluminescence measurements, enabling relative comparison of the generation processes of singlet and triplet excitons. As a result, the generation ratio of singlet excitons is shown to be enhanced by applied voltage. The enhancement is concluded to result from the increase of the generation rate in signlet excitons induced by electric field.